Gambaran Pelaksanaan Anc (Antenatal Care) Pada Ibu Hamil Di Masa Pandemi Covid-19 Di Puskesmas Kandangan, Temanggung - Desiana Dwi Utami; Heni Setyowati Esti Rahayu; Robiul Fitri Masithoh (Prosiding University Research Colloquium, 2021)
The current pandemic has a major impact on all groups, including vulnerable groups of pregnant women, pregnant women experience partial immunity due to physiological changes during pregnancy. Antenatal Care is an effort to prevent maternal and fetal death and can detect high-risk pregnancies early. ANC visits should be made at least 4 times during her pregnancy. ANC visits at the Kandangan Health Center for mothers in Trimester 1 and Trimester 2 are quite low, but visits in Trimester 3 are fairly good and routine. This study aims to obtain an overview of Antenatal care for pregnant women during the Covid-19 pandemic at the Kandangan Health Center. This research design uses descriptive. The number of respondents was 96 pregnant women, the sampling technique was purposive sampling, the research instrument used a questionnaire. data analysis using univariate. The results of the study showed that the highest age who made visits was 20-35 years (49.0%), mothers with the highest parity were 54 respondents (56.3%), the most mothers were mothers who did not work as many as 80 respondents (83%), and the highest gestational age was 7 months (42.7%). The distribution of the highest ANC visits was for 3rd trimester mothers (75%), and for the availability of ANC services, pregnant women had received all services, only 7 respondents did not consume FE tablets, due to normal HB laboratory results. [Century 10 pt, italic]